The Influence of Proximity Service on Citizen Satisfaction with Public Services - Melawati, Fitri; Agustina, Wiwit; Parinduri, Ramadha Yanti; Suryandari, Ratnawati Yuni; Idris, Dany Luqyana (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to determine the effect of proximity service on citizen satisfaction with public services. This study uses a quantitative approach. The population in this study amounted to 397 respondents. The sampling technique used probability sampling with a simple random sampling method, resulting in a sample of 40 respondents. The data collection method used in this study was a questionnaire and literature study. The analysis method used was simple linear regression. The results of the study indicate that proximity service has a positive and significant effect on citizen satisfaction with public services. From the results of the correlation coefficient calculation, a Pearson correlation coefficient value of 0.518 was obtained. This indicates that there is a fairly strong relationship between Proximity service and Citizen Satisfaction with public services. Then the results of the determination coefficient calculation show an R square of 0.268, which means that the citizen satisfaction variable can be explained by the proximity service variable, which is 26.8%. While the remaining 73.2% is explained by other variables.